Capability of Sabhara Two-Wheel Patrol Personnel to Prevent Theft at Bogor Police - Negara, Dani Kusuma (Indonesian Journal of Police Studies, 2024)
This research has a background in which the Bogor Police who receive incoming reports every day related to the theft of motorized vehicles that disturb the public. Even though some preemptive and preventive efforts have been made by Bogor Police officers so that these crimes can be avoided. One of the efforts made by the Bogor Sabhara Police Unit is through the patrol of two-wheeled motor vehicles. But in reality the Kamtibmas disturbance is still happening. This study aims to determine the activities of the two-wheeled Sabhara Patrol Unit in the Bogor Police area, whether it has been effective or not, with issues such as: the ability of Sabhara Police Bogor personnel to conduct two-wheeled patrol, how to act on the sabhara two-wheeled patrol in overcoming wheel curanmor two in the jurisdiction of Bogor Police and What are the factors that influence the way of acting sabhara two-wheeled patrol in tackling two-wheeled carburetor in the Bogor Police jurisdiction. This research uses a qualitative approach. Data collection techniques carried out by interview, observation and document research. As for the analysis that is used include data reduction, data presentation and conclusion drawing. Based on the results of the study, it can be concluded that the ability of Sabhara Bogor Police Personnel in Conducting Two-Wheeled Patrol, is less than optimal because competently consisting of Self Concept / Attitude, Knowledge and Skill, then how to act in sabhara two-wheeled patrol In dealing with two-wheeled curanmor adapted to management aspects, while the way of acting Sabhara two-wheeled patrol in overcoming two-wheeled curanmor in the Bogor Police jurisdiction is influenced by internal and external aspects that include Strengths, Weaknesses, Opportunities and Threats. The advice given is to improve communication training, create SOPs and HTCK specifically for the Two Wheel Patrol activities, increase cooperation with the Intelligence and Binmas functions to provide actual information about criminal acts of Curanmor and increase cooperation with Sat PP Bogor Regency to conduct joint patrol activities.